O estado de perigo no novo Código Civil / The state of peril in the new Brazilian Civil Code - Ferraz, Pedro Conpany (REVISTA QUAESTIO IURIS, 2014)
Trabalho recebido e avaliado pelo Conselho executivo da Revista Quaestio Iuris <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Resumo <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">O presente artigo pretende colaborar no cenário jurídico brasileiro com uma análise doutrinária de um antigo vício dos negócios jurídicos que veio a ser positivado recentemente com o Código Civil de 2002, o estado de perigo. Esta pesquisa perpassa por análise da legislação estrangeira, analisando as fontes de inspiração do legislador. Ademais, ousa em estabelecer um conceito a este instituto, delimitando seus elementos constituintes. Baseado nos elementos levantados, traça a natureza jurídica deste instituto, diferenciando-o de outros vícios do negócio jurídico, como a lesão, a fraude e a coação. Além disso, a partir da perspectiva civil-constitucional, aponta as conseqüências práticas desta relevante inovação do código civil na sociedade consumerista. <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Palavras-chave <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Negócio jurídico – vício – perigo <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Abstract <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">The article intends to collaborate to the Brazilian legal scene by the doctrinal analysis of an old vice of the legal transactions that came to be recently incorporated in the Civil Code of 2002, the state of peril. This research makes an analysis of the foreign legislation, taking into account the legislator’s sources. Besides, it dares establishing a concept to this institute, delimiting its constitutive elements. Based on these elements, it traces the legal nature of this institute, differentiating it from other vices of the legal transaction, as the injury, the fraud and the coercion. Moreover, from the civilian-constitutional perspective, it points out the practical consequences of this relevant innovation of the civil code in a consumerist society. <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Keywords <p class="Paragraph SCX224293601" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Legal agreement – vice – peril